Why Does Centralisation Fail to Internalise Policy Externalities? - R Dur; Hein J. Roelfsema (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2004)
We provide an explanation for why centralisation of political decision making results in overspending in some policy domains, whereas toolow spending persists in others. We study a model in which delegates from jurisdictions bargain over local public goods provision. If all of thecosts of public goods are shared through a common budget, policymakers delegate bargaining to `public good lovers', resulting inoverprovision of public goods. If a sufficiently large part of the costs can no be shared, underprovision persists because policy makers delegate bargaining to `conservatives'. We derive financing rules that eliminate the incentives for strategic delegation.Keywords: Centralised decision making, strategic delegation, financing rules.
Keywords: 330; Centralised decision making; strategic delegation; financing rules